Pengaruh berat telur, luas permukaan, dan berat jenis, terhadap shape index telur puyuh (Coturnix coturnix japonica) - Atika Nuriza Tanaffasa; Wiwin Tanwiriah; Dani Garnida (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
The research was held from 6th April 2023 to 6th Mei 2023 in Laboratory of Poultry Poduction, Padjadjaran University. The purpose of this research was to figure out the corellations between weight, surface area, and specific gravity on the shape index of quail eggs (Coturnix Coturnix Japonica). The method used in this research is corellational, and path analysis, with exogenous variables they are weight (X1), surface area (X2), specific gravity (X3) and one endogenous variable is shape index(Y). Sampling collects by purposive sampling with the criteria of eggshell integrity and uniform egg weight. The data obtained from the measurement results were then carried out the normality test, linearity test, Pearson correlation and path analysis. The results showed that the weight and surface area of the quail egg shape index has a correlation value of -0.194. Specific gravity with shape index quail eggs showed a correlation value of 0.013. Weight gives the greatest effect on the shape index of quail eggs (Coturnix Coturnix Japonica) by 7.51%, surface area gives the effect on the shape index of quail eggs (Coturnix Coturnix Japonica) by 0.62% and specific gravity gives a low effect on the shape index of quail eggs (Coturnix Coturnix Japonica) 0.03%.